Is Individualized Medicine More Cost-Effective? A Systematic Review - Hatz, Maximilian H. M.; Schremser, Katharina; Rogowski, Wolf H. (PharmacoEconomics, 2014)
Background Individualized medicine (IM) is a rapidly evolving field that is associated with both visions of more effective care at lower costs and fears of highly priced, low-value interventions. It is unclear which view is supported by the current evidence. Objective Our objective was to systematically review the health economic evidence related to IM and to derive general statements on its cost-effectiveness. Data sources A literature search of MEDLINE database for English- and German-language studies was conducted. Study appraisal and synthesis method Cost-effectiveness and cost-utility studies for technologies meeting the MEDLINE medical subject headings (MeSH) definition of IM (genetically targeted interventions) were reviewed. This was followed by a standardized extraction of general study characteristics and cost-effectiveness results. Results Most of the 84 studies included in the synthesis were from the USA ( n = 43, 51 %), cost-utility studies ( n = 66, 79 %), and published since 2005 ( n = 60, 71 %). The results ranged from dominant to dominated. The median value (cost-utility studies) was calculated to be rounded $US22,000 per quality-adjusted life year (QALY) gained (adjusted to $US, year 2008 values), which is equal to the rounded median cost-effectiveness in the peer-reviewed English-language literature according to a recent review. Many studies reported more than one strategy of IM with highly varying cost-effectiveness ratios. Generally, results differed according to test type, and tests for disease prognosis or screening appeared to be more favorable than tests to stratify patients by response or by risk of adverse effects. However, these results were not significant. Limitations Different definitions of IM could have been used. Quality assessment of the studies was restricted to analyzing transparency. Conclusions IM neither seems to display superior cost-effectiveness than other types of medical interventions nor to be economically inferior. Instead, rather than ‘whether’ healthcare was individualized, the question of ‘how’ it was individualized was of economic relevance.